Relationship between the level of physical activity and sedentary, overweight and health-related quality of life in scholar-age asthmatic children: an explanatory study in Seville - Alfonso Rosa, Rosa María; Del Pozo-Cruz, Borja; González Limones, Francisco Javier; Del Pozo-Cruz, Jesús; Del Pozo-Cruz, Borja; Del Pozo-Cruz, Jesús; González Limones, Francisco Javier; Alfonso Rosa, Rosa María (FEADEF, 2012)
The aim of this study was: 1) To determine the differences between normal-weight asthmatic children and overweight asthmatic children in terms of HRQoL and amount of physical activity and sedentary and 2) To determine the relationship between amount of physical activity, sedentary and BMI and their influence on the HRQoL of this population in Seville. Method. We used a cohort design study that included 69 school-age children with controlled persistent asthma. The measures included in the study were: the questionnaire PAQL (S), to assess the HRQoL of children and the IPAQ-A questionnaire to assess the amount of physical activity and sedentary lifestyle of children. BMI was also calculated and determined if the participant was of normal-weight or overweight. Results. Overweight children scored worse on HRQoL and IPAQ-A values than their peers with normal-weight. Positive correlations were also observed between BMI and the amount of sedentary lifestyle. Negative correlations were observed between BMI and the amount of physical activity and also negative correlations were observed between BMI and HRQoL. Conclusion. BMI negatively affect HRQoL in school- age asthmatic children